Phlebotomy resulting in controlled hypovolemia to prevent blood loss in major hepatic resections (PRICE-2): study protocol for a phase 3 randomized controlled trial - Martel, Guillaume; Lenet, Tori; Wherrett, Christopher; Carrier, François-Martin; Monette, Leah; Workneh, Aklile; Brousseau, Karine; Ruel, Monique; Chassé, Michaël; Collin, Yves; Vandenbroucke-Menu, Franck; Hamel-Perreault, Élodie; et al. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Introduction Blood loss and red blood cell (RBC) transfusion in liver surgery are areas of concern for surgeons, anesthesiologists, and patients alike. While various methods are employed to reduce surgical blood loss, the evidence base surrounding each intervention is limited. Hypovolemic phlebotomy, the removal of whole blood from the patient without volume replacement during liver transection, has been strongly associated with decreased bleeding and RBC transfusion in observational studies. This trial aims to investigate whether hypovolemic phlebotomy is superior to usual care in reducing RBC transfusions in liver resection. Methods This study is a double-blind multicenter randomized controlled trial. Adult patients undergoing major hepatic resections for any indication will be randomly allocated in a 1:1 ratio to either hypovolemic phlebotomy and usual care or usual care alone. Exclusion criteria will be minor resections, preoperative hemoglobin <100g/L, renal insufficiency, and other contraindication to hypovolemic phlebotomy. The primary outcome will be the proportion of patients receiving at least one allogeneic RBC transfusion unit within 30 days of the onset of surgery. Secondary outcomes will include transfusion of other allogeneic blood products, blood loss, morbidity, mortality, and intraoperative physiologic parameters. The surgical team will be blinded to the intervention. Randomization will occur on the morning of surgery. The sample size will comprise 440 patients. Enrolment will occur at four Canadian academic liver surgery centers over a 4-year period. Ethics approval will be obtained at participating sites before enrolment. Discussion The results of this randomized control trial will provide high-quality evidence regarding the use of hypovolemic phlebotomy in major liver resection and its effects on RBC transfusion. If proven to be effective, this intervention could become standard of care in liver operations internationally and become incorporated within perioperative patient blood management programs. Trial registration ClinicalTrials.gov NCT03651154 . Registered on August 29 2018.